Representasi Ekologis pada Buku Teks: Analisis Wacana Kritis untuk Kesadaran Ekologis - Ruruh Sarasati (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
Ecological literacy is an important part of forming an environmentally conscious generation. One way to foster ecological literacy is to include ecological components in student books in schools. This research analyzes the texts in Indonesian textbooks from the perspective of Critical Discourse Analysis. The Critical Discourse Analysis used in this research is Norman Fairclough's Critical Discourse Analysis. There are three dimensions of critical discourse analysis study, namely text analysis, text production analysis, and social practice analysis. Data collection was carried out using the read and labelling technique. The results showed that text analysis has represented ecology and ecological awareness, while text production analysis and social practice analysis are still limited to ecological elements, not yet referring to the current situation in the field.